In Situ Oxygen Generation Enhances the SCAP Survival in Hydrogel Constructs. (September 2021) - Zou, T.; Jiang, S.; Zhang, Y.; Liu, J.; Yi, B.; Qi, Y.; Dissanayaka, W.L.; Zhang, C.
Prolonged and severe hypoxia is the main cause of death of transplanted cells prior to the establishment of functional circulation. In situ generation of oxygen by oxygen-producing scaffolds—a unique solution that could produce and deliver oxygen to the adjacent cells independently of blood perfusion—has attracted considerable attention to enhance the survivability of the transplanted cells. However, the application of oxygen-generating scaffolds for facilitating cell survival in pulp-like tissue regeneration is yet to be explored. In this study, gelatin methacryloyl (GelMA)—a biocompatible scaffolding material that closely mimics the native extracellular matrix and is conducive to cell proliferation and differentiation—was used to fabricate oxygen-generating scaffolds by loading various concentrations of CaO2 . The CaO2 distribution, topography, swelling, and pore size of CaO2 -GelMA hydrogels were characterized in detail. The release of O2 by the scaffold and the viability, spreading, and proliferation of stem cells from apical papilla (SCAPs) encapsulated in the GelMA hydrogels with various concentrations of CaO2 under hypoxia were evaluated. In addition, cellular constructs were engineered into root canals, and cell viability within the apical, middle, and coronal portions was assessed. Our findings showed that 0.5% CaO2 -GelMA was sufficient to supply in situ oxygen for maintaining the embedded SCAP viability for 1 wk. Furthermore, the 0.5% CaO2 -GelMA hydrogels improved the survivability of SCAPs within the coronal portion of the engineered cellular constructs within the root canals. This work demonstrated that 0.5% CaO2 -GelMA hydrogels offer a potential promising scaffold that enhances survival of the embedded SCAPs in endodontic regeneration.